ANALISIS PENGGUNAAN TEKNOLOGI INFORMASI (INTERNET) TERHADAP MASYARAKAT DI KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Yusuf, Intje (Katalogis, 2016)
This research aims at finding out and analyzing the use of information technology (internet) to enrich the perception and knowledge to the society in Sigi Biromaru District and the positive and negative impacts of using the information technology (internet) to the society at Sigi Biromaru District, Sigi Regency. 100 respondents were taken as the samples of this research. The data were collected through interview, observation, questioner and documentation. Moreover, they were analyzed descriptively with a quantitative approach, in which the results are described and in detail. T-test analysis was used to answer the first problem of this research and Chi-Square (Ï‡2) analysis was used to answer the second problem of this research. The results show that: 1). Information technology (internet) gives a big influence toward to the development of the perception and knowledge to the society at Sigi Biromaru District, Sigi Regency. 2) Information technology (internet) gives a positive and negative impacts to the society at Sigi Biromaru District, Sigi Regency, nevertheless the positive impact are more dominant than the negative impact.